2022
DOI: 10.1101/gr.275864.121
|View full text |Cite
|
Sign up to set email alerts
|

Distal regulation, silencers, and a shared combinatorial syntax are hallmarks of animal embryogenesis

Abstract: The chromatin environment plays a central role in regulating developmental gene expression in metazoans. Yet, the ancestral regulatory landscape of metazoan embryogenesis is unknown. Here, we generate chromatin accessibility profiles for six embryonic, plus larval and adult stages in the sponge Amphimedon queenslandica. These profiles are reproducible within stages, reflect histone modifications, and identify transcription factor (TF) binding sequence motifs predictive of cis-regulatory elements operating duri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…"Distal" enhancers are characterized as such regions that can be found a certain distance from the closest transcription start site, a metric that is implemented variably, e.g. 800 bp [23], 500 bp [55], 300 bp [53], and 200 bp [54]. (C) The phylogenetic distribution of chromatin marks, genes, and genomic features related to the functionality of enhancers does not support the origin of distal enhancers in the animal stem lineage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…"Distal" enhancers are characterized as such regions that can be found a certain distance from the closest transcription start site, a metric that is implemented variably, e.g. 800 bp [23], 500 bp [55], 300 bp [53], and 200 bp [54]. (C) The phylogenetic distribution of chromatin marks, genes, and genomic features related to the functionality of enhancers does not support the origin of distal enhancers in the animal stem lineage.…”
Section: Discussionmentioning
confidence: 99%
“…About 75% of these tested enhancers were validated in reporter assays, in which the expression pattern of a heterologous construct for a putative enhancer was similar to the in situ staining pattern for the mRNA of the nearest gene. In the sponge Amphimedon queenslandica, patches of H3K4me1 enrichment more than 200 bases from transcription start sites identified several putative regulatory sites [54], while ATAC-seq profiling of A. queenslandica development showed that ~60% of dynamically regulated ATAC-seq peaks are >500 bp from transcription start sites [55].…”
Section: Did the First Animals Expand Or Invent The Use Of Distal Enh...mentioning
confidence: 99%
“…However, ectopic gene expression may lead to lineage skewing and other unwanted outcomes. Cell-type-specific enhancers are conserved across evolution and can potentially be used to restrict transgene expression 71,72,6 . Indeed, erythroid-specific GATA1 enhancers can drive restricted expression of GATA1 to rescue erythroid differentiation in Diamond-Blackfan Anaemia 73 .…”
Section: Discussionmentioning
confidence: 99%
“…However, ectopic gene expression, particularly in stem cells, may lead to lineage skewing and other unwanted outcomes. Cell-type-specific enhancers are conserved across evolution and can potentially be used to limit gene expression to particular cell populations (Cornejo-Paramo et al, 2022;Goode et al, 2016;Xu et al, 2012). Indeed a recent report has described the use of erythroid-specific GATA1 enhancers to drive restricted expression of GATA1 to rescue erythroid differentiation in Diamond-Blackfan Anaemia, an approach that is agnostic to the precise genetic mutation in individual patients (Voit et al, 2022).…”
Section: Therapeutic Implications For Bone Marrow Failure Syndromesmentioning
confidence: 99%